Categorical properties of iterated power (2001)
In [2], the class of the Lawson monads was introduced which contains sufficiently wide class of monads and have a functional representation. Unfortunately, the powers monads are not in this class. We introduce in this paper the iterated power monad and show that it is a Lawson monad.